Matrix Metalloproteinase‑8 Expression and Collagen Density Alterations in Male and Female Rat Models of Porphyromonas gingivalis‑Induced Periodontitis - Agustin Wulan Suci Dharmayanti; Zahara Meilawaty; Amandia Dewi Permana Shita; Sari Setyaningsih; Pudji Astuti; Dwi Warna Aju Fatmawati; Benni Benyamin; Suhartini; Tantin Ermawati; Endah Aryati Eko Ningtyas; Ani Subekti (Jurnal Kesehatan Gigi, 2026)
Periodontitis is periodontal tissue inflammation caused by periodontal pathogens, including Porphyromonas gingivalis (P.gingivalis). The incidence of periodontitis in men and women differs significantly, especially in the severity of periodontal tissue destruction, if it overrules smoking habits and poor oral hygiene. However, the information was inadequate and debatable. This study aimed to compare the effect of P. gingivalis on periodontal tissue destruction in female and male rat models, showing increased MMP-8 expression and decreased collagen density. This study was a laboratory experiment using male and female Wistar rats. Each gender of animal models was divided into two groups: control and periodontitis. The periodontitis group induced P. gingivalis every three days for 19 days in the distopalatal and distobuccal gingival sulcus of the mandibular first molar. After the final induction, they were euthanized, and their mandibles were removed for histological observation by immunohistochemistry to determine the expression of MMP-8 in periodontal tissue and Picrosirius Red to determine collagen density. Expression of MMP-8 was observed at 400x magnification using a light microscope, whereas collagen density was observed at 400x magnification; the images were analyzed using the ImageJ application. The data were analyzed using ANOVA and a multiple-comparison test (p<95%). The results revealed that male and female periodontitis models showed significant differences in MMP-8 expression and collagen density (p<0.05). Briefly, P. gingivalis caused periodontal tissue damage in female and male periodontitis models, whereas the female periodontitis model experienced more periodontal tissue damage than the male.